2021
DOI: 10.1177/13634607211028517
|View full text |Cite
|
Sign up to set email alerts
|

Gay monuments in queer times: Amsterdam’s Homomonument and the politics of inclusive social practice

Abstract: Despite growing debate about the role of monuments in diverse societies, there has been insufficient attention to contestations that have emerged involving ‘gay’ or ‘queer’ monuments. This article examines the politics of inclusion and exclusion that can stem from the social practices that evolve around these monuments, particularly as the imperatives and priorities of LGBTQ (lesbian, gay, bisexual, transgender and queer) activism evolve while monuments, created in a particular historical and geographical cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…For example, our own collaborative research activities (e.g., Greatrick et al, 2022; Zebracki et al, 2021) and those considered by diverse LGBTQ+‐identified contributors to our dedicated Pride in the Field blog series in Geography Directions (see Zebracki & Greatrick, 2021b) display how LGBTQ+ people themselves are naturally experts at navigating the field. They develop practices and ways of being in the field that offer some hope to an otherwise rather gloomy picture.…”
Section: Claiming Lgbtq+ Spaces In the Fieldmentioning
confidence: 99%
“…For example, our own collaborative research activities (e.g., Greatrick et al, 2022; Zebracki et al, 2021) and those considered by diverse LGBTQ+‐identified contributors to our dedicated Pride in the Field blog series in Geography Directions (see Zebracki & Greatrick, 2021b) display how LGBTQ+ people themselves are naturally experts at navigating the field. They develop practices and ways of being in the field that offer some hope to an otherwise rather gloomy picture.…”
Section: Claiming Lgbtq+ Spaces In the Fieldmentioning
confidence: 99%